Resource Governance and Developmental States in the Global South
XVIII, 251 p.
Keywords: The political economy landscape has shifted as multinational corporations increase their investment efforts, changing the geographies of extraction. The contributors make the argument for the need of new theoretical perspectives anchored in critical political economy to address structural dynamics in the global industry.